Safeguarding Constitutional Rights in Regional Elections: An Analysis of Violation Handling by Bawaslu Bone in the 2024 Election - Ariyanti, Liza; Sari , Muspita; Darliana, Darliana (IAIN Bone, 2025)
Safeguarding constitutional rights in regional elections is essential to Indonesia’s democratic integrity. This study analyzes the handling of violations in the 2024 Bone Regency election, focusing on the effectiveness and challenges of the Election Supervisory Board (Bawaslu). Employing a qualitative juridical-empirical approach, data were obtained from regulations, official reports, and interviews. Of 19 alleged violations, only 11 were registered as most reports failed to meet procedural requirements. Electoral criminal offenses dominated, while administrative violations were minimal. Bawaslu’s effectiveness was constrained by limited resources, short deadlines, and weak institutional coordination. Constitutional Court Decision No. 104/PUU-XXIII/2025, which elevated Bawaslu’s recommendations to binding decisions, reinforced its role in protecting voters’ rights. The study concludes that electoral oversight functions as a constitutional safeguard for electoral justice. It recommends strengthening institutional capacity, expanding digital monitoring, and enhancing public legal literacy to sustain democratic integrity.